Menguak Faktor-Faktor Dalam Mengaktualisasikan Perilaku Caring di Era Pandemi Covid-19 - Ni Made Henna Juli Astuti; Agus Fredy Maradona (Universitas Pendidikan Nasional, 2022)
The quality of hospital services is influenced by human resource factors. Human resources who are in direct contact with patients are nurses. Nurses are at the forefront of dealing with patients 24 hours a day, therefore quality, qualified nursing resources are needed and capable of caring behavior. Caring behavior is the essence of nursing that distinguishes nurses from other professions. The phenomenon that occurred in the era of the covid-19 pandemic had an impact on the high workload experienced by nurses due to an increase in the number of patients, thus affecting nurses in actualizing caring behavior. This study aims to identify what factors influence nurses in actualizing caring behavior in the era of the covid-19 pandemic. The study was designed as an observational study using cross sectional data collection methods. The instrument used is a questionnaire filled out by respondents determined by random sampling. The sample consisted of 139 respondents, namely nurses in the Inpatient Room at the Bali Mandara Hospital, Bali Province. The data analysis technique used in this study was SPSS Version 25.0 and Amos for Windows 23.0, starting with the evaluation process of SEM assumptions through an evaluation of the normality of the data, confirmatory factor analysis (CFA) and analysis of the effect with SEM. The results of this study indicate that there is a significant positive influence between leadership, organizational culture and work environment on job satisfaction. There is a significant positive influence between leadership, organizational culture and work environment on the caring behavior of nurses. And there is a significant positive effect between job satisfaction and caring behavior of nurses.